Private tubewell development and groundwater markets in Pakistan: a district-level analysis - Meinzen-Dick, Ruth S. (Pakistan Institute of Development Economics, 1994)
Groundwater irrigation, which was developed in the 1960s to increase vertical drainage to prevent waterlogging and salinisation in canal commands, has now become a major component of the overall irrigation sector in Pakistan. An estimated 37 percent of total irrigation supplies at the farm gate comes from groundwater [NESPAK (1991)]. Along with the shift in purpose for groundwater development from providing drainage to providing irrigation supplies, has come a shift from public to private tubewells as the primary source of groundwater in Pakistan. The increase in private tubewells has not only increased the total availability of water for crop production, but also provided farmers with greater control over irrigation supplies. Because groundwater from private tubewells is generally not tied to the rigid warabandi schedule of canal deliveries, water applications can be more closely matched to crop requirements. The result is higher yields and higher economic returns to irrigated agriculture [Meinzen-Di